The rehabilitation efficacy of diaphragmatic breathing combined with limb coordination training for lower limb lymphedema following gynecologic cancer surgery - Wang, Jingxin; Ma, Jiahui; Zhang, Yujie; Tian, Yuan; Wang, Xinxin; Wang, Yu; Xiang, Dongquan; Wang, Daoyu; Huang, Kun; Mao, Luxi; Zhang, Jiaxin; Fan, Huixuan; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Objective To explore the effect of diaphragmatic breathing combined with limbs training on lower limb lymphedema after gynecological cancer surgery. Methods From January 2022 to May 2022, a total of 60 patients with lower limb lymphedema following gynecologic cancer surgery were selected and divided into a control group (n=30) and a treatment group (n=30). The control group received comprehensive decongestive therapy (CDT) for managing lower limb lymphedema after gynecologic cancer surgery, while the treatment group received diaphragmatic breathing combined with limb coordination training in addition to CDT. Both groups underwent a four-week treatment cycle. The assessment involved the evaluation of lower limb lymphedema symptoms using the Genital, Lower Limb, Buttock, and Abdomen Score (GCLQ), measurements of bilateral lower limb circumference, and anxiety and depression scores. Results Compared with CDT alone, the scores of the self-perceived symptom assessment questionnaire (GCLQ), bilateral lower limb circumference and anxiety and depression scores of patients treated with diaphragmatic breathing combined with limb linkage training were significantly reduced. Conclusion Diaphragmatic breathing combined with limb coordination training can further expedite and enhance the effectiveness of treating lower limb lymphedema following gynecologic cancer surgery.